The Urbanization and Vernacular Housing in the Villa de San Antonino Castillo Velasco, Oaxaca, Mexico - Mayorga-Hernández, José Israel (Corporación Universitaria del Caribe, CECAR., 2021)
Aspects such as exponential urban growth and the lack of congruent public policies for the conservation of vernacular dwellings, have a direct impact on the extinction of vernacular housing in communities such as the Villa de San Antonino Castillo Velasco, Oaxaca, Mexico. The objective of the research is to identify and register the vernacular dwellings in the study site, for their conservation. The methodology used is mixed. The main finding was a total of 1,394 homes for private use, of which 156 conserve vernacular adobe typology. Therefore, the recognition and protection of the governments to the vernacular housing, is conjunctural to bequeath it to the future generations, as identity and integral patrimony of the cultural landscape.